Fatness of children and adolescents from various socio-economic groups between 1978 and 1988 - Lipowicz, Anna (Polskie Towarzystwo Antropologiczne, 1999)
The study material contains the data on boys and girls aged from 6 to 18 years located in the course of the Third and Fourth Anthropological Surveys carried out in Poland in 1977/78 and 1987/88. The questionnaire data (father's and mother's education and number of children in the family) were supplemented with the results of measurements of the triceps skinfold. It is assumed that the triceps skinfold is a good indicator of the nutritional status. In both studies fatness of children decreased along with a decreasing level of parents' education and with increasing family size. Triceps skinfold size was related mainly to the number of children in the family. In the decade from 1978 to 1988 a decline in social differences with regard to fatness of children coming from various socio-economic strata was observed.